Polígonos e poliedros equidecomponíveis - Fernandes, Flavia Mescko (2018)
We show in this work the Wallace-Bolyai-Gerwien theorem and Hilbert’s third problem. We use the first to proof by equicomposition the area of plane geometric figures and the second to show that the demonstration of relations for volumes can not always be done by equicomposition. Also, we have analyzed some textbooks of Basic Education to evaluate how much equicomposition is used to establish relations for areas and volumes. We also suggest ludic-manipulative activities for Elementary and High School by exploring the equicomposition in two and three dimensions.